Resilience of Sme Business: Lesson Learn From Creative Climate, Digital Literacy, And Innovation Capability - Sri Handari Wahyuningsih; Alni Rahmawati; Marsudi Endang (International Journal of Science and Environment (IJSE), 2025)
Micro, Small and Medium Enterprises (MSMEs) are one of the businesses that play a significant role in the Indonesian economy. For this reason, the capacity to survive needs to be a concern and priority. This research aims to analyze the direct determinants of organizational resilience, namely creative climate and digital literacy, as well as indirect determinants, namely innovation. This research took 151 Small Medium Enterprises (SME) through a quantitative approach. The analysis technique used is Regression with Path Analysis Stages.Through the Path Analysis stage, the research results prove that a creative climate is able to directly and indirectly encourage organizational resilience. Digital Literacy is able to encourage organizational resilience through full mediation, namely Innovation. This research does not prove the role of innovation as a mediating influence of digital literacy on organizational resilience.MSMEs In the current recovery period, it is necessary to increase organizational resilience by creating a creative climate that will increase innovation capabilities. Apart from that, mastering the use of systems and strategies using digital technology will also encourage innovation capabilities and business resilience.